A new stone occlusion device for upper ureteral calculi: Preliminary clinical outcomes. Issue 5 (September 2012) - Feng, Chen-Chen; Wu, Zhong; Jiang, Hao-Wen; Ding, Qiang
Abstract: Aim: To evaluate the efficacy and safety of the newly developed stone occlusion device in preventing retropulsion of upper ureteral calculi during laser lithotripsy. Methods: A prospective randomized trial of 59 patients with upper ureteral calculi was conducted. Group I consisted of 27 patients using the new device. Group II consisted of 32 patients using the NTrap, a well studied and extensively used occluder. All patients underwent ureteroscopic Ho:YAG laser lithotripsy and operational parameters were compared in-between. Results: Neither group had any obvious complications. There were no differences in operation time ( p = 0.6881), intraoperative success rate (100%, respectively), postoperative stone-free rate ( p = 1.000), or overall success rate ( p = 1.000) between the two groups. Conclusion: This new device is clinically parallel to the effectiveness and safety of NTrap but is available at half the price and is clinically valid for extensive use. However, more investigations are warranted to confirm the efficacy and to contribute to device modification.